2017
DOI: 10.1128/jvi.00219-17
|View full text |Cite
|
Sign up to set email alerts
|

BST-2 Expression Modulates Small CD4-Mimetic Sensitization of HIV-1-Infected Cells to Antibody-Dependent Cellular Cytotoxicity

Abstract: Antibodies recognizing conserved CD4-induced (CD4i) epitopes on human immunodeficiency virus type 1 (HIV-1) Env and able to mediate antibodydependent cellular cytotoxicity (ADCC) have been shown to be present in sera from most HIV-1-infected individuals. These antibodies preferentially recognize Env in its CD4-bound conformation. CD4 downregulation by Nef and Vpu dramatically reduces exposure of CD4i HIV-1 Env epitopes and therefore reduce the susceptibility of HIV-1-infected cells to ADCC mediated by HIV-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 60 publications
5
49
0
Order By: Relevance
“…3A). This phenomenon has been well established and is due to the accumulation of BST-2trapped viral particles at the cell surface, which results in Env accumulation (9,12,14). In agreement with their CD4-induced nature, the recognition of infected cells by the nNAbs tested (A32, 17b, N12-i2, and N5-i5) was dramatically enhanced by deletion of Nef and Vpu.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…3A). This phenomenon has been well established and is due to the accumulation of BST-2trapped viral particles at the cell surface, which results in Env accumulation (9,12,14). In agreement with their CD4-induced nature, the recognition of infected cells by the nNAbs tested (A32, 17b, N12-i2, and N5-i5) was dramatically enhanced by deletion of Nef and Vpu.…”
Section: Resultssupporting
confidence: 63%
“…It is becoming increasingly clear that several factors contribute to ADCC responses against HIV-1-infected cells, i.e., Env conformation (38), CD4 (8,9,11) and BST-2 (12)(13)(14) downregulation, gp120 shedding (37,59), and the stability of Env-Ab complexes at the cell surface (60), which are driven by the affinity of Abs for Env (61), Env internalization (15), cell surface expression of stress ligands (56,62), and now antibody-induced Env internalization. Additional work will be required to tease apart the differential contribution of each of these factors in ADCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have also described only limited efficacy, typically Ͻ30%, of ADCML (67) and ADCC of HIV-1-infected cell lines by NK effector cells (40,42). Blockade of CD59 yields increased complement-mediated lysis (67, 68), whereas attenuated viruses, deficient for Nef and Vpu expression, displayed enhanced susceptibility to ADCC of infected cells in a tetherin-dependent manner (40,63). Consistent with this, we found that ADCML-and ADCC-sensitive HIV-1-infected CD4 T cells were phenotypically in the early stage of infection, i.e., displayed high CD4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This protective role of ADCC in elite controllers highlights the importance of ADCC in vivo and identifies it as a correlate of control in HIV-1 infection. Vpu and Nef also downregulate BST2 (tetherin), a restriction factor that anchors virions onto the surface of infected CD4 T cells, thus increasing surface density of viral antigens and leading to enhancement of antibody-antigen interactions (40,58,63). Additionally, both HIV-1 virions and infected cells utilize surface regulators of complement activation, such as CD55 and CD59, to resist complement-mediated lysis (34,(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%